Penerapan Strategi Promosi Kesehatan dalam Pencegahan Stunting di Puskesmas Air Besar Kota Ambon - Abd Rijali Lapodi; Herlien Sinay (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
At the Air Besar Ambon Community Health Center there were 55 cases of stunting, which of course require serious treatment strategies, including health promotion strategies in preventing stunting. The aim of this research was to explore more in-depth information regarding advocacy, building an atmosphere and empowering the community in preventing stunting at the Air Besar Ambon Community Health Center. This type of research was a qualitative study involving informants selected using a purposive sampling technique. The key informant was the head of the community health center, apart from that there were 3 supporting informants and a main informant, namely an employee in the health promotion sector. Data was collected through interviews, documentation studies and field notes. After the data is collected, content analysis is then carried out. The results of the research show that advocacy, atmosphere building and community empowerment in preventing stunting at the Air Besar Ambon Health Center were carried out with the involvement of health promotion programs as well as cross-program and cross-sectoral issues. It was concluded that the health promotion strategy in preventing stunting does not only involve health promotion programs, but also all sectors including the health service, posyandu cadres and the community.Keywords: stunting; health promotion; advocacy; build atmosphere; empowerment ABSTRAK Di Puskesmas Air Besar Ambon terdapat 55 kasus stunting, yang tentunya memerlukan strategi penanganan yang serius, termasuk strategi promosi kesehatan dalam pencegahan stunting. Tujuan penelitian ini adalah menggali informasi lebih mendalam terkait advokasi, bina suasana, dan pemberdayaan masyarakat dalam pencegahan stunting di Puskesmas Air Besar Ambon. Jenis penelitian ini merupakan studi kualitatif yang melibatkan para informan yang dipilih dengan teknik purposive sampling. Informan kunci adalah kepala puskesmas, selain itu ada 3 informan pendukung dan seorang informan utama yakni pegawai bidang promosi kesehatan. Data dikumpulkan melalui wawancara, studi dokumentasi dan catatan lapangan (field note). Setelah data terkumpul selanjutnya dilakukan analisis konten. Hasil penelitian menunjukkan bahwa advokasi, bina suasana, dan pemberdayaan masyarakat dalam pencegahan stunting di Puskesmas Air Besar Ambon terlaksana dengan keterlibatan program promosi kesehatan maupun lintas program dan lintas sektoral. Disimpulkan bahwa strategi promosi kesehatan dalam pencegahan stunting, tidak hanya melibatkan program promosi kesehatan, tetapi juga semua sektor baik dari dinas kesehatan, kader-kader posyandu dan masyarakat.Kata kunci: stunting; promosi kesehatan; advokasi; bina suasana; pemberdayaan